Hari Raya Yahudi Sebagai Representasi Kesadaran Historis Dan Keagamaan Bangsa Israel - Mayyadi; Naya Maulidia; Ahmad Jais (4, 2026)
Jewish holidays are crucial for understanding Judaism, not only as a theological belief system but also as a manifestation of the historical consciousness of the Israelite people. In Judaism, religious celebrations are always closely linked to historical events, understood as manifestations of God's intervention in the life of the Israelite people. The history of salvation, experiences of liberation, wanderings, and even the steadfastness of faith amidst suffering are not simply remembered as past events but are re-enacted through holiday celebrations. Therefore, Jewish holidays cannot be understood simply as formal ritual practices, but as a means of maintaining collective memory and strengthening the religious identity of the Jewish people. This research uses a descriptive qualitative method with a literature review approach, analyzing various books and scholarly journals that discuss Jewish history, ritual, and religious identity. This approach allows researchers to comprehensively explore the relationship between holiday celebrations, historical narratives, and the formation of Israel's religious consciousness. The results of the study indicate that Jewish holidays function as a medium for actualizing sacred history, where past events are re-enacted through symbols, prayers, and repeated ritual practices. Through this mechanism, history is not only studied but also experienced existentially by the people. Holiday celebrations serve as a space for the effective transmission of values ​​and meaning, thus preserving the historical consciousness of the Israeli people and passing it on from one generation to the next. Thus, Jewish holidays play a crucial role in strengthening the continuity of Jewish religious identity in contemporary religious life. Abstrak Hari raya dalam tradisi Yahudi merupakan aspek yang sangat penting untuk memahami agama Yahudi tidak hanya sebagai sistem kepercayaan teologis, tetapi juga sebagai manifestasi kesadaran historis bangsa Israel. Dalam Yudaisme, perayaan keagamaan selalu berkaitan erat dengan peristiwa-peristiwa sejarah yang dipahami sebagai bentuk campur tangan Tuhan dalam perjalanan hidup bangsa Israel. Sejarah keselamatan, pengalaman pembebasan, pengembaraan, hingga keteguhan iman di tengah penderitaan tidak sekadar dikenang sebagai peristiwa masa lalu, melainkan dihadirkan kembali melalui perayaan hari raya. Oleh karena itu, hari raya Yahudi tidak dapat dipahami hanya sebagai praktik ritual formal, tetapi sebagai sarana pemeliharaan ingatan kolektif sekaligus penguatan identitas keagamaan umat YahudiPenelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan studi kepustakaan, dengan menganalisis berbagai buku dan jurnal ilmiah yang membahas sejarah, ritual, serta identitas keagamaan Yahudi. Pendekatan ini memungkinkan peneliti menelusuri keterkaitan antara perayaan hari raya, narasi sejarah, dan pembentukan kesadaran religius bangsa Israel secara komprehensif. Hasil kajian menunjukkan bahwa hari raya Yahudi berfungsi sebagai media aktualisasi sejarah suci, di mana peristiwa-peristiwa masa lalu dihadirkan kembali melalui simbol, doa, dan praktik ritual yang dilakukan secara berulang. Melalui mekanisme ini, sejarah tidak hanya dipelajari, tetapi dialami secara eksistensial oleh umat. Perayaan hari raya menjadi ruang transmisi nilai dan makna yang efektif, sehingga kesadaran historis bangsa Israel terus terjaga dan diwariskan dari satu generasi ke generasi berikutnya. Dengan demikian, hari raya Yahudi berperan penting dalam memperkuat kesinambungan identitas keagamaan umat Yahudi dalam kehidupan keagamaan kontemporer